Educational Change in Alberta, Canada - Webber, Charles F. (Education Policy Analysis Archives, 1995)
Alberta, Canada, is the site of large-scale educational change initiatives legislated by the provincial government. The mandates have sparked heated public debate over the appropriateness, wisdom, and utility of the reforms. This article summarizes the views of representatives of several educational interest groups and offers suggestions for making change more meaningful and successful.